2019
DOI: 10.1007/978-3-030-17402-6_2
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Explorer Who Returns to the Base

Abstract: In this paper we study the problem of exploring a temporal graph (i.e. a graph that changes over time), in the fundamental case where the underlying static graph is a star. The aim of the exploration problem in a temporal star is to find a temporal walk which starts at the center of the star, visits all leafs, and eventually returns back to the center. We initiate a systematic study of the computational complexity of this problem, depending on the number k of time-labels that every edge is allowed to have; tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Theorem 1 (Akrida et al [1]). RTB Temporal Graph Exploration is NP-complete, when the underlying graph is a star, and each edge exists in at most six graphs G i , and the start and end vertex is the center of the star.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Theorem 1 (Akrida et al [1]). RTB Temporal Graph Exploration is NP-complete, when the underlying graph is a star, and each edge exists in at most six graphs G i , and the start and end vertex is the center of the star.…”
Section: Introductionmentioning
confidence: 99%
“…In this note, we study the complexity of a problem on temporal networks: the Temporal Graph Exploration problem. Recently, Akrida et al [1] showed that this problem is NP-complete, even when the underlying graph is a star. An important special case, studied by Erlebach et al [5], is when at each point in time, the current graph is connected.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations